Grasi dalam Perspektif Hukum Islam dan Hukum Positif Indonesia - Imdadurrouf Imdadurrouf (Sharia Faculty of State Islamic University of Prof. K.H. Saifuddin Zuhri, Purwokerto, 2010)
As one of the rights owned by the president, clemency is controlled by the Indonesian Constitution, UUD 1945. In Islamic law there is also a possibility to forgive one’s mistake in the name of justice and truthful.